Strato-mesospheric carbon monoxide profiles above Kiruna, Sweden (67.8 ° N, 20.4 ° E), since 2008 - Ryan, Niall J.; Palm, Mathias; Raffalski, Uwe; Larsson, Richard; Manney, Gloria; Millán, Luis; Notholt, Justus (Earth System Science Data, 2018)
This paper presents the retrieval and validation of a self-consistent time series of carbon monoxide (CO) above Kiruna using measurements from the Kiruna Microwave Radiometer (KIMRA). The data set currently spans the years 2008–2015, and measurements are ongoing at Kiruna. The spectra are inverted using an optimal estimation method to retrieve altitude profiles of CO concentrations in the atmosphere within an average altitude range of 48–84 km. Atmospheric temperature data from the Special Sensor Microwave Imager/Sounder aboard the US Air Force meteorological satellite DMSP-F18, are used in the inversion of KIMRA spectra between January 2011 and May 2014. This KIMRA CO data set is compared with CO data from the Microwave Limb Sounder aboard the Aura satellite: there is a maximum bias for KIMRA of ∼ 0.65 ppmv at 68 km (corresponding to 14.7 % of the mean CO value at 68 km) and a maximum relative bias of 22 % (0.44 ppmv) at 60 km. Standard deviations of the differences between profiles are similar in magnitude to the estimated uncertainties in the profiles. Correlations between the instruments are within 0.87 and 0.94. These numbers indicate agreement between the instruments. To expand the CO data set outside of the lifetime of DMSP-F18, another inversion setup was used that incorporates modelled temperatures from the European Centre for Medium-Range Weather Forecasts. The effect on the retrieved CO profiles when using a different temperature data set in the inversion was assessed. A comparison of the two overlapping KIMRA CO data sets shows a positive bias of < 5 % in the extended data set and a correlation > 0.98 between the lower retrievable altitude limit and 82.5 km. The extended data set shows a larger range ( ≤ 6 %) of CO concentrations that is not explained by random error estimates. Measurements are continuing and the extended KIMRA CO time series currently spans 2008–2015, with gaps corresponding to non-operation and summer periods when CO concentrations below ∼ 90 km drop to very low values. The data can be accessed at doi:10.1594/PANGAEA.861730 .